Профессор Жамбатырова Г.Ш. – ученый, педагог, наставник - Мансуров, З. А. (International relations and international law Journal, 2016)
Professor Zhambatyrova G.Sh. is the scientist, the teacher, the mentor Жамбатырова Г.Ш. профессор - ғалым, ұстаз, жетекші ретінде